Student's Reading Interest in University of Bangka Belitung - Laila Hayati; Novyandra Ilham Bahtera (Faculty of Social and Political Sciences University of Bangka Belitung, 2019)
Indonesia is one of countries that has high quantity of people but low in quality. It is shown from the low rating in human development index. Thus, the quality improvement i.e. educational improvement should be implemented effectively. Reading is one of the most crucial element in the field of education. The low rating of reading interest among Indonesian people becomes a tremendous issue which needs to be solved. To tackle, government implements the reading movement as contained in Act of the Republic of Indonesia number 20 of 2003 and ruled by Ministry of Culture and Education (Permendikbud) number 23 of 2015 about 15 minutes of literacy activities prior to the beginning of the study session. The study aims to identify the university students’ reading interest in University of Bangka Belitung as well as to examine the determinant and the obstacle of the university students’ reading interest. Structured questionnaire and online data collection methods were employed to obtain the primary data from 182 university students in University of Bangka Belitung, Indonesia. The study showed that the reading interest of university students in University of Bangka Belitung were at low score. About one-third of the respondents visited library once a week, one-fourth visited library twice a week and only 8.3 % of the respondents visited library 4 – 5 times a week. Almost one-fourth of respondents had 1 – 4 reading materials. Around half of respondents read less than an hour a day. As the determinant of book reading and library attendance, 61.3 % of the respondents were due to do assignment while only 16 % of respondents were due to habit and need to read. Whereas, as the obstacle to reading, almost half of respondents preferred using gadget, around one-fourth of respondents spent their times with friends and 39.2 % of respondents were too busy with their extracurricular activities on campus